Sustained Reduction in Third-generation Cephalosporin Usage in Adult Inpatients Following Introduction of an Antimicrobial Stewardship Program in a Large, Urban Hospital in Malawi. (15th February 2020) - Lester, Rebecca; Haigh, Kate; Wood, Alasdair; MacPherson, Eleanor E; Maheswaran, Hendramoorthy; Bogue, Patrick; Hanger, Sofia; Kalizang'oma, Akuzike; Srirathan, Vinothan; Kulapani, David; Mallewa, Jane; Nyirenda, Mulinda; et al.
Abstract: Background: Third-generation cephalosporins (3GC) remain the first-choice empiric antibiotic for severe infection in many sub-Saharan African hospitals. In Malawi, the limited availability of alternatives means that strategies to prevent the spread of 3GC resistance are imperative; however, suitable approaches to antimicrobial stewardship (AMS) in low-income settings are not well studied. Methods: We introduced an AMS intervention to Queen Elizabeth Central Hospital in Blantyre. The intervention consisted of a prescribing application for smartphones and regular point-prevalence surveys with prescriber feedback. We evaluate the effects of the intervention on 3GC usage and on the cost of providing antibiotics. Using a thematic analysis of semi-structured interviews and participant observations, we additionally evaluate the acceptability of the stewardship program. Results: The proportion of antibiotic prescriptions for a 3GC reduced from 193/241 (80.1%) to 177/330 (53.6%; percentage decrease, 26.5%; 95% confidence interval, 18.7–34.1) with no change in the case-fatality rate. The cost analysis estimated an annual savings of US15 000. Qualitative research revealed trust in the guideline and found that its accessibility through smartphones helpful to guide clinical decisions. Operational health-system barriers and hierarchal clinical relationships lead to continued reliance on 3GC. Conclusions: We report the successful introduction of an antimicrobial stewardship approach in Malawi. By focusing on pragmatic interventions and simple aims, we demonstrate the feasibility, acceptability, and cost savings of a stewardship program where resources are limited. In doing so, we provide a suitable starting point for expansions of AMS interventions in this and other low-income settings. Abstract : An antimicrobial stewardship program, consisting of a prescribing guideline and point-prevalence surveys with prescriber feedback, was introduced at Queen Elizabeth Central Hospital in Malawi. The program was effective in reducing third-generation cephalosporin usage and was potentially cost-saving for the hospital.